UPAYA PENINGKATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMPN 7 SAMPANG - Suyono (re-JIEM (Research Journal of Islamic Education Management), 2021)
The quality of learning is determined by the quality of the teacher. The more competent teachers are, the more they can provide services to students well. Teacher competence can continue to be developed with academic supervision activities carried out by school principals. Therefore, school action research was conducted with the aim of improving the quality of learning. This research is School Action Research conducted at SMPN 7 Sampang. Collecting data by observation, interviews, documentation and tests. The results of the study show the quality of learning with indicators, namely: 1) the ability of teachers to prepare lesson plans, 2) the use of learning media, and 3) online teaching skills can be improved through academic supervision at SMPN 7 Sampang. This is evidenced in the first cycle of teacher competence in making lesson plans with a medium and high success rate of 64.29%, increasing to 85.71 in the second cycle. Competence using online media has a medium and high success rate of 71.43% in the first cycle increasing to 92.86% in the second cycle and online teaching competence with a medium and high success rate of 64.29% in the first cycle increasing to 85.71 in cycle II so that it is proven that academic supervision can improve the quality of learning at SMPN 7 Sampang